A multiplexed high throughput screening assay using flow cytometry identifies glycolytic molecular probes in bloodstream form Trypanosoma brucei - Daniel H. Call; John Asafo Adjei; Ryan Pilgrim; James W. Jeong; E. Vance Willis; Ronald A. Zegarra; Nicholas L. Tapia; Madalyn Osterhaus; Jacob A. Vance; Charles M. Voyton; James A. Call; Sabrina S. Pizarro; et al. (International Journal for Parasitology: Drugs and Drug Resistance)
Kinetoplastid organisms, including Trypanosoma brucei, are a significant health burden in many tropical and semitropical countries. Much of their metabolism is poorly understood. To better study kinetoplastid metabolism, chemical probes that inhibit kinetoplastid enzymes are needed. To discover chemical probes, we have developed a high-throughput flow cytometry screening assay that simultaneously measures multiple glycolysis-relevant metabolites in live T. brucei bloodstream form parasites. We transfected parasites with biosensors that measure glucose, ATP, or glycosomal pH. The glucose and ATP sensors were FRET biosensors, while the pH sensor was a GFP-based biosensor. The pH sensor exhibited a different fluorescent profile from the FRET sensors, allowing us to simultaneously measure pH and either glucose or ATP. Cell viability was measured in tandem with the biosensors using thiazole red. We pooled sensor cell lines, loaded them onto plates containing a compound library, and then analyzed them by flow cytometry. The library was analyzed twice, once with the pooled pH and glucose sensor cell lines and once with the pH and ATP sensor cell lines. Multiplexing sensors provided some internal validation of active compounds and gave potential clues for each compound's target(s). We demonstrated this using the glycolytic inhibitor 2-deoxyglucose and the alternative oxidase inhibitor salicylhydroxamic acid. Individual biosensor-based assays exhibited a Z′-factor value acceptable for high-throughput screening, including when multiplexed. We tested assay performance in a pilot screen of 14,976 compounds from the Life Chemicals Compound Library. We obtained hit rates from 0.2 to 0.4% depending on the biosensor, with many compounds impacting multiple sensors. We rescreened 44 hits, and 28 (64%) showed repeatable activity for one or more sensors. One compound exhibited EC50 values in the low micromolar range against two sensors. We expect this method will enable the discovery of glycolytic chemical probes to improve metabolic studies in kinetoplastid parasites.